Padrão de financiamento da indústria de papel e celulose no Brasil nos anos 1990 - Silva, Paulo Roberto de Souza Trajano da (2007)
This work analyzes financing patterns of paper and pulp industry in Brazil in the 1990 s, trying to identify any shifts in those patterns, occurred since economic liberalization, remembering that this work considered liberalization process in Brazil as starting in 1990. The background for this analysis is the comparison with some of the main producing countries in paper and pulp, observing not only the history of this industry on those countries, but also industrial financing systems organized there. Finishing this research, some indicators were developed for a sample of brazilian paper and pulp companies, with the intent of finding about the behavior of this industrial sector in the 1990 s, highlighting its capital structure